Transcriptional read-through is not sufficient to induce an epigenetic switch in the silencing activity of Polycomb response elements - Erokhin, Maksim (Proc Natl Acad Sci U S A, 2015)
In Drosophila, Polycomb (PcG) and Trithorax (TrxG) group proteins are assembled on Polycomb response elements (PREs) to maintain tissue and stage-specific patterns of gene expression. Critical to coordinating gene expression with the process of differentiation, the activity of PREs can be switched “on” and “off.” When on, the PRE imposes a silenced state on the genes in the same domain that is stably inherited through multiple rounds of cell division. When the PRE is switched off, the domain is in a state permissive for gene expression that can be stably inherited. Previous studies have suggested that a burst of transcription through a PRE sequence displaces PcG proteins and provides a universal mechanism for inducing a heritable switch in PRE activity from on to off; however, the evidence favoring this model is indirect. Here, we have directly tested the transcriptional read-through mechanism. Contrary to previous suggestions, we show that transcription through the PRE is not sufficient for inducing an epigenetic switch in PRE activity. In fact, even high levels of continuous transcription through a PRE fails to dislodge the PcG proteins, nor does it remove repressive histone marks. Our results indicate that other mechanisms involving adjacent DNA regulatory elements must be implicated in heritable switch of PRE activity.